PENGABDIAN MASYARAKAT UNTUK INSTALASI AIR BERSIH SISTEM HIDROSTATIK BAGI RUKUN WARGA BERISIKO BALITA STUNTING DI DESA KUALIN, KABUPATEN TTS - Lada, Christina Olly; Woda, Rahel Rara; Lidia, Kartini; Johannis, Amanda Jelita Eka Riani (Universitas Nusa Cendana, 2025)
Water is a basic human need and access to clean water will improve a person’s health. However, some communities have limited access to clean water. Difficulty in obtaining clean water will increase the risk of infectious disease transmission and reduce the food security of families and communities, especially in rural areas. These two things certainly increase the risk of stunting in children. This is also a problem in Kualin Village. Therefore, Kualin Village became a Community Service Intervention Village particularly in providing clean water. The activity was carried out in Hamlet 4, Kualin Village, South Central Timor Regency with involvement of participants such as Kualin Village residents, JPM staff and experts, and from FKKH Undana lecturers. The IbM project was divided into few stages, began with an initial survey to determine the initial condition of the damaged water network. Subsequently, a follow-up survey was carried out to determine and calculate the analysis of equipment and tools requirements related to the damaged water network. This activity was preceded by community outreach to inform the position and location of the damaged plumbing system and repair plans. The survey results were then used as standards for improving and implementing clean water installations. After the water installation was repaired, a trial of its use was carried out, which was then followed by the formation of a work team and water committee comprised of the officials and residents of Kualin Village to ensure the continuity of this project, which is expected to improve the well-being and health of Kualin Village residents